Peran Orang Tua dalam Membentuk Karakter Anak pada Zaman Sekarang - Dini Silvina; Selvi Yulianis; Gusmaneli Gusmaneli (Universitas Palangka Raya, 2025)
Education is the main means for humans to develop and show their existence as humans. One of the factors that causes education in humans is the factor of parents. Children basically have habits (education) as well as the habits of their parents. As a child, of course, he will always follow the behavior of his parents, namely the habits of his parents. The purpose of education in the family is for children to develop well, covering all aspects of child development, namely intellectual, physical and spiritual. Another goal is to assist schools or other educational institutions in developing the personality of their students. Parents play an important role in shaping children's character. In this case, parents are an example for their children in behaving, behaving, and facing problems in their lives.